2022
DOI: 10.1007/s11606-022-07800-1
|View full text |Cite
|
Sign up to set email alerts
|

Early Impact of VA MISSION Act Implementation on Primary Care Appointment Wait Time

Abstract: Background Through Community Care Networks (CCNs) implemented with the VA MISSION Act, VA expanded provider contracting and instituted network adequacy standards for Veterans’ community care. Objective To determine whether early CCN implementation impacted community primary care (PC) appointment wait times overall, and by rural/urban and PC shortage area (HPSA) status. Design Using VA administrative data from Februa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 28 publications
3
10
0
Order By: Relevance
“…9,11 Despite the comparatively modest percentage increases in veterans' utilization of VA, the much larger number of veterans using VA vs CC for primary care during the MISSION Act period indicated that reliance on VA for primary care continued to remain strong, mitigating concerns that the MISSION Act would contribute to privatization of VA care. 5,6,9 we found some interesting differences in utilization among race and ethnicity categories. Although Black and Hispanic veterans had higher percentage increases in CC utilization Abbreviation: ARR, adjusted risk ratio.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…9,11 Despite the comparatively modest percentage increases in veterans' utilization of VA, the much larger number of veterans using VA vs CC for primary care during the MISSION Act period indicated that reliance on VA for primary care continued to remain strong, mitigating concerns that the MISSION Act would contribute to privatization of VA care. 5,6,9 we found some interesting differences in utilization among race and ethnicity categories. Although Black and Hispanic veterans had higher percentage increases in CC utilization Abbreviation: ARR, adjusted risk ratio.…”
Section: Discussionmentioning
confidence: 75%
“…[18][19][20][21] Third, as expected, CC unadjusted mean wait times decreased substantially during the MISSION Act period for all veterans; however, CC unadjusted mean wait times remained consistently longer than those in VA, which was similar to findings from other studies and other outpatient care services. 6,12,17 VA and CC unadjusted mean wait times exceeded the 20-day wait time standards established in the MISSION Act. 35 Because primary care plays a key role in providing preventive care and managing and coordinating veterans' health care, 9,10,36 reducing wait times is essential for optimizing veterans' overall health and well-being.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations